Isolasi dan Identifikasi Mikroba Penyebab Kontaminasi dari Udara di Laboratorium Kultur Jaringan Tumbuhan UIN-SU Medan - Sucahyo, Ahmad Imam; Manalu, Kartika; Nasution, Rizki Amelia (Jurnal Biologi, 2023)
Plant tissue culture laboratory is a technique for growing cells, tissues or slices of plant organs which are often called explants in the laboratory in an artificial media containing aseptic (sterile) nutrients to become a whole plant. This research aims to know the isolation and identification of contaminating microbes in the plant tissue culture laboratory and to know the types of contaminating microbes in the plant tissue culture laboratory. This research was conducted from december 2022 to january 2023 at the Wahdatul Ulum plant tissue culture laboratory, uinsu medan with 5 main sampling points.the sampling point consists of an incubation room, planting room and practicum space which is divided into 3 collection points. Staining tests and biochemical tests are conducted at the USU faculty of mathematics and natural sciences microbiology laboratory. The results of the study found 23 bacterial isolates that contamined the wahdatul ulum plant tissue culture laboratory at UINSU Medan consisting of the genera bacillus, lactobacillus, streptobasil, aeromonas, pseudomonas, serratia, bacteroides and acinetobacter while the contaminating fungi were Mucor sp. Contamination occurs due to mobility and activity in the laboratory room.